A Comparative Study on Behavior of RC Columns Strengthened by CFRP and Steel Jacket - Ibraheem Rawaa S. (EDP Sciences, 2021)
This paper studies the behavior of axially loaded RC columns which are confined with carbon fiber reinforced polymers’ sheet (CFRP) and steel jackets (SJ). The study is based on twelve axially loaded RC columns tested up to failure. It is divided into three schemes based on its strengthening type; each scheme has four columns. The main parameters in this study were the compressive strength of the concrete and steel reinforcement ratio. Furthermore, the results of the experimental test showed a substantial enhancement in the column's load-carrying capacity. When compared to the original columns, the CFRP sheet had a significant effect on improving the ductility of the column by increasing the axial deformation by about 59.2 to 95.7%. On the other hand, the SJ contributed mostly to the column load-carrying capacity, which increased the capacity of RC concrete from 75 to 107%; because of its composite action comparing with the CFRP sheet action in which unidirectional lateral confinement is provided. Both methods produced completely different failure modes. The columns strengthened with CFRP sheet failed by rupture occurring in the sheet fibers. The strengthened with SJ failed due to the buckling that occurred in the steel angles due to the direct contact with the head of the column, and crushing in the concrete has occurred.